Application of Quality Function Deployment in Development of Products Pottery: A Case Study of Pottery Community Enterprise in Nakhon Si Thammarat Province: 1 Faculty of Engineering, Rajamangala University of Technology Srivijaya, 2 Faculty of Engineering, Princess of Naradhiwas University - Rawangwong, Surasit; Homkhiew, Chatree; Boonchouytan, Worapong; Chattong, Jaknarin; Tehyo, Muhamad (Princess of Naradhiwas University Journal, 2019)
This research examined the application of the quality function deployment (QFD) process in the product planning phase, in order to develop pottery productsthat meet the customer’s exact needs. The customers’ needs were collected through 180 questionnaires, then they were classified, using both affinity diagrams and tree diagrams. The purpose of this classification was to analyze the customers’ needs and to develop product prototypes based on the quality function deployment process. According to the study, the main factors that the customers considered as priorities in choosing pottery were: 1) Thai identity, 2) harmless material, 3) beautiful and modern aspect, 4) reasonable price, 5) local identity, and 6) diverse styles. Knowing the characteristics of pottery products from the QFD process, the community pottery enterprise then applied these to the design of new pottery products. Afterwards, a new product satisfaction survey was conducted among pottery users. The product satisfaction was alsomeasured among customers and selling agent stores. The result of this research revealed that the average satisfactory values of all new types of products were increased greater than the old products from 3.241 to 4.028 points or increased about 0.787 points, it is to say by 24.3%.